2020
DOI: 10.1007/s13201-020-01250-y
|View full text |Cite
|
Sign up to set email alerts
|

Desorption of chromium (VI) and lead (II) ions and regeneration of the exhausted adsorbent

Abstract: The desorption characteristics of previously adsorbed hexavalent chromium [Cr(VI)] and divalent lead [Pb(II)] ions on groundnut husk were tested by various desorption eluents such as tap water, de-ionized water, NaOH, HCl and H2SO4. Among them, HCl and H2SO4 were chosen as the best desorbing agents for Cr(VI) and Pb(II) ions, respectively, due to their high desorption efficiency. The desorption efficiency of HCl and H2SO4 for Cr(VI) and Pb(II) ions was about 76.1% and 82.1%, respectively, at a concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…This may be ascribed to the fact that an increase in the concentration of HNO 3 caused increases in the number of H + in solution, which increases the concentration gradient of the metal ions and H + and therefore increases the driving force for ion exchange, which favored metal ions during the desorption process. 107 The results in this study corroborate the analysis of Bayuo et al 108 who reported similar values using 0.1 mol L −1 H 2 SO 4 (82.1%) and HCl (74.2%) for desorption of Pb(II). Similar results have been reported by Samson et al, 109 who studied desorption using different concentrations of HCl (0.01, 0.1, 1.0 and 1.20 mol L −1 ).…”
Section: Thermodynamic Evaluation Of Adsorption Processsupporting
confidence: 90%
See 2 more Smart Citations
“…This may be ascribed to the fact that an increase in the concentration of HNO 3 caused increases in the number of H + in solution, which increases the concentration gradient of the metal ions and H + and therefore increases the driving force for ion exchange, which favored metal ions during the desorption process. 107 The results in this study corroborate the analysis of Bayuo et al 108 who reported similar values using 0.1 mol L −1 H 2 SO 4 (82.1%) and HCl (74.2%) for desorption of Pb(II). Similar results have been reported by Samson et al, 109 who studied desorption using different concentrations of HCl (0.01, 0.1, 1.0 and 1.20 mol L −1 ).…”
Section: Thermodynamic Evaluation Of Adsorption Processsupporting
confidence: 90%
“…Despite the success in the use of nanomaterials for the removal of pollutants from wastewater, the discharge of adsorbents that have been exhausted is a serious environmental issue 27 . As a result, it is critical to regenerate and reuse adsorbents to make the adsorption process economically and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each adsorbent was regenerated by mixing the used adsorbent with 5% HCl (10 mL) as the desorption agent and this desorption of adsorbed contaminant ions from the GO material will restore the adsorbents for future use. 42 The desorption mixture was sonicated for 30 min and the adsorbent material was then washed with M.Q. water 3 times after removing the supernatant, and dried at 50 °C for 6 h. The regeneration cycles proved an ability to remove the dyes and antibiotics from aqueous solutions as a valid reusable material.…”
Section: Methodsmentioning
confidence: 99%
“…Supercapacitor electrodes made of polyacrylonitrile exhibit superior conductivity, high power density, and enhanced capacitance. [29]…”
Section: Supporting Information Summarymentioning
confidence: 99%